Effects of Temperature and Humidity on the Fitness of Aphid Parasitoid, Binodoxys communis - Shike Xia; Ningwei Ma; Peiling Wang; Yanhui Lu (Insects)
Binodoxys communis is a dominant endoparasitoid of aphids in cotton fields, yet empirical evidence on how temperature and humidity regulate its growth, development, and reproduction remains limited. To address this gap, we assessed the effects of both constant and fluctuating temperature, as well as various combinations of temperature and humidity, on the longevity, parasitism, and fecundity of this parasitoid. Our results revealed that adult longevity of B. communis was longer at 20 °C and 25 °C while significantly shortened at a high temperature (35 °C). Similarly, the parasitism rate, female ratio, emergence duration, and offspring longevity of the parasitoid were all superior at 20 °C and 25 °C compared to 15 °C and 35 °C. Moreover, the longevity of both male (6.96 ± 0.10 d) and female (6.88 ± 0.07 d) parasitoids was significantly extended at 25 °C and 60% RH. Temperature had a marked impact on the parasitic capability of parasitoids, with the number of Aphis gossypii parasitized daily by B. communis being significantly higher at 25 °C than at 15 °C and 35 °C. Nevertheless, humidity and the interaction between humidity and temperature had no significant influence on parasitic capacity. The parasitism of B. communis followed the Holling-II model, with the highest daily maximum parasitism observed at 25 °C. In conclusion, our study showed that 25 °C positively enhanced the fitness of B. communis, providing a valuable reference for indoor population expansion and field release of B. communis, potentially enhancing its effectiveness as a biological control agent against aphids.